Analisis Likuiditas Dan Profitabilitas Serta Pengaruhnya Terhadap Struktur Modal Perusahaan - Nur Iftitah Arung (Jurnal Ilmiah Bongaya, 2024)
This study aims to determine the impact of liquidity and productivity on funding development in sub-section providers of consumption and mineral water listed on the Indonesia Stock Exchange. In addition, information collection uses optional information obtained from the organization's annual financial report which can be accessed through the website www.idx.co.id. The population in this study is known that the producer organization in the field of consumption and mineral water listed on the Indonesia Stock Exchange during 2009-2001 totaling 30 organizations, while the sample taken is known that 15 organizations with an examination strategy using a purposive test. The information handled is 45 examples that have been tried for traditional assumptions such as ordinary assumptions, multicollinearity, heteroscedasticity, and autocorrelation. The information investigation strategy uses various relapse methods. The exploration results show that Liquidity is significantly related to Funding Construction and Benefits are significantly related to Funding Design.